Blood–brain barrier peptide shuttles. (June 2017) - Sánchez-Navarro, Macarena; Giralt, Ernest; Teixidó, Meritxell
Graphical abstract: Highlights: Targeting of the BBB is a great opportunity for brain delivery of therapeutics. BBB peptide shuttles can target both passive and active transport mechanisms present at the BBB. BBB-shuttles targeting passive transport are adequate for getting small molecules into the brain. Targeting active transport is more appropriate for macromolecules and nanoparticles. Development of protease-resistant approaches is broadening the applicability BBB-shuttles. Abstract : Brain delivery is hampered by the presence of the blood–brain barrier (BBB), a natural defence of the brain that protects it and allows the entrance of nutrients by several mechanisms. Taking advantage of these mechanisms is an opportunity to treat brain related diseases. Among the different alternatives, BBB peptide shuttles are gaining attention to increase brain delivery of therapeutics. The most recent advances in the field are analysed here.